Cuantificación y extracción de pectina a partir de los desechos de cáscara de fruta (2017)
The treatment of agribusiness wastes, as well as the implied monetary loss generates the need to look for alternatives for their use. In this work, it is studied the possibility of obtaining pectin as value added product from the fruit peel. First, the content of pectin in 5 different fruit peels was quantified, to be able to determine the pectin?s recovery and process yield of different pectin extraction protocols, likewise, the acid type influence was evaluated in these protocols